Виробництво оптичного скла 1-ої категорії пузирності у керамічних судинах - Петров, Дмитро Вікторович; Філоненко, Сергій Вікторович; Брагіна, Людмила Лазарівна (НТУ "ХПІ", 2017)
Показана актуальність розробки та впровадження нових технологічних методів підвищення якості оптичного скла для використання його як у цивільних галузях, так і у приладах оборонної сфери. Проаналізовано існуючі методи підвищення якості скла за пузирністю та виявлено їх недоліки при виробництві оптичного скла марки БК (баритовий крон). Здійснено розробку ефективного та економічного методу виробництва цього скла останнім циклом при його багатопередільному наварі із забезпеченням якості першої категорії за пузирністю. Наведені результати промислових випробувань та впровадження розробленого методу виробництва оптичного скла марки БК.

The urgency of the development and implementation of new technological methods for improving the quality of optical glass improving for its use in both civilian and defense equipment sectors is shown. The technological complexity of the production of the barite crown due to the high concentration (up to 35%) BaO is substantiated. The purpose of the work is to create a new technological method, which allows produce an optical glass of the first category of bubbles. According to industrial results, existing methods for improving the quality of optical glass of bubbles were considered. Existing methods fully fulfill the conditions of the task for the production of other types of optical glass (K-8, K-108 type). But the production of a barite crown in a pot furnace involves the active formation of gas in the melt, which requires the removal of the foam layer from its surface. Therefore, existing methods have significant drawbacks in the optical glass BC production. After studying the technological processes of optical glass-making, a new technological method has been implemented that achieves the required quality of bubbles and justifies its economic expediency. The main essence of the new method is the production of a barite crown by the last cycle in the multi-cycle melting of optical glasses similar in composition. To fully implement the method, it is necessary to correct the composition barite crown’s batch to prevent the crystalline phase formation . The new method allows to abandon the production and use of ceramic crucibles with the expensive synthetic protective layer. The results of the industrial researches and introduction optical glass grade BC are presented.
Production of optical glass of the 1st category of bubbles in ceramic crucibles
Keywords: крон баритоновий; система оптико-електронна; виробництво багатоциклічне; продукція; optical glass; barite crowns; optoelectronic systems; multi-cycle production; products